Dostosowania organizacyjne i ekonomiczne w leśnictwie po przystąpieniu Polski do Unii Europejskiej - Radwan, Andrzej (Organizational and Economic Adjustments in Forestry after Poland's Accession to the European Union, 2005)
Polish forestry has been realizing a concept of sustainable and multifunctional forest management resulting according to the law on forests and programme of the State Forest Policy from 1997.Implementation of the regulations mentioned above may incur growing costs of activities in forestry due to non-market character of the non-productive, i.e. ecological and social functions which forests fulfill. Adjusting forestry to free market requirements involves its deep restructuring connected with growing personal costs and other factors of forest production. In the analysed period employment in forestry has decreased considerably owing to the development of private services.Further reforms for improvement of management efficiency will be necessary in the process of adjusting this sector of economy to the EU requirements. It is also caused by progressing globalization and liberating of raw wood and wood product market, and increasingly greater divergence between growing costs of production and simultaneous tendency of declining wood prices.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 239-244